HOMO DEUS: THE ISLAMIC CRITICAL APPROACH TO THE NEW AGENDA OF HUMANITY ACCORDING TO HARARI - Azizah, Nur; Habibi, Jauharul; Maria, Galuh; Shuhada, Muhammad Aula Rahmad (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2024)
This article discusses Islam and homo deus as a new agenda for humanity’s future. This article tries to explain the reading of homo deus and the problems of humanity in the future. Likewise, regarding the issue of immortality and human happiness in the future from an Islamic perspective. This article tries to analyze the problem using the library research model in carrying out an analysis of the main problem. Humans to fight death and the problems that humans expect in the future to maintain eternity feel like a god who will live eternally in the world. It is not only immortality in the world that modern humans will achieve, but how humans live in the world and gain happiness. True happiness is difficult for humans to obtain, even though humans use the discoveries of modern science. Humans will truly find happiness if they believe in and draw closer to God. The happiness that modern humans feel is only temporary pseudo-happiness.  The immortality that modern humans desire is not directly proportional to happiness. This can be seen from the large number of people dying by suicide in various countries, the majority of which are advanced, and technology is developing rapidly, but it still cannot help their spiritual problems. Modern humans think that everything can be solved with the modern science they have discovered, even though there is God’s intervention in life in this world.